2021
DOI: 10.3390/ijerph18084242
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Environment in Coronary Artery Disease

Abstract: In recent years, studies evaluated the associations between coronary artery disease (CAD) and fecal gut microbiota composition. This opens new perspectives on therapeutic strategies to prevent CAD representing the leading cause of mortality in Western societies. We have conducted a review of the literature regarding the characteristics of the gut microbiota of CAD patients, its underlying mechanisms and their associations with pollution and the Western diet. The latest evidence confirms that an abnormal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 104 publications
0
12
0
Order By: Relevance
“…Recent data demonstrated that COVID-19 patients have significant differences in gut microbiota composition and on the interaction between microbiota and host cells [ 73 ]. On the other side, as described in the introduction section, gastrointestinal dysbiosis can lead to cardiovascular diseases [ 2 , 3 , 77 ] and cardiovascular impairment can contribute to maintain gut microbiota dysbiosis [ 78 ]. In particular, many studies have described cases of patients with COVID-19 and inflammatory cardiomyopathies.…”
Section: Final Remarksmentioning
confidence: 99%
“…Recent data demonstrated that COVID-19 patients have significant differences in gut microbiota composition and on the interaction between microbiota and host cells [ 73 ]. On the other side, as described in the introduction section, gastrointestinal dysbiosis can lead to cardiovascular diseases [ 2 , 3 , 77 ] and cardiovascular impairment can contribute to maintain gut microbiota dysbiosis [ 78 ]. In particular, many studies have described cases of patients with COVID-19 and inflammatory cardiomyopathies.…”
Section: Final Remarksmentioning
confidence: 99%
“…However, serious side effects have been reported in using statins, such as rhabdomyolysis, liver toxicity, and a higher risk for new-onset diabetes ( 5 ). Recent studies have also explored the role of gut microbiota and its derived metabolites (such as short-chain fatty acids [SCFAs], trimethylamine-N-oxide [TMAO], bile acids) in the pathogenesis of CAD ( 6 ), and a large body of evidence supports that the gut microbiota composition and its activity might play a role in atherosclerosis ( 7 ). The “gut-heart axis” via bidirectional communications between the gut and the heart together achieve cardiac homeostasis, and recent studies have shed new insight into the intricate mechanisms of CAD ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although coronary artery disease and type 2 diabetes mellitus have also been proven to affect cardiac remodeling, these topics are beyond the scope of our review. To date, there is a huge amount of data, concerning the role of GMB in the pathogenesis and progression of type 2 diabetes mellitus and coronary heart disease (3971 and 312 publications over the last 5 years, respectively) [ 10 , 11 ]. To our opinion, these topics are well described elsewhere [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%